1995
DOI: 10.2136/sssaj1995.03615995005900050021x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Soil Water Content and Temperature on Nitrification and Aeration

Abstract: Environmental concerns have stimulated increased interest in NO−3 accumulation in soils. The aeration status of the soil, which is mainly governed by the water content and temperature, is a central factor. The biological process responsible for NO−3 accumulation, nitrification, was measured to estimate the combined effects of water content and temperature and determine their joint effect on soil aeration. The effects of temperatures of 15, 20, 25, 30, and 35°C and water contents equivalent to 0.35, 0.42, 0.50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 0 publications
3
45
1
1
Order By: Relevance
“…In addition, soil CO 2 efflux, another process comprising autotrophic and heterotrophic respiration, was nearly doubled at the transplanted sites. Consistently, it has been well documented that soil nitrification and CO 2 efflux are strongly affected by climate changes (Grundmann et al, 1995;Davidson et al, 1998).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, soil CO 2 efflux, another process comprising autotrophic and heterotrophic respiration, was nearly doubled at the transplanted sites. Consistently, it has been well documented that soil nitrification and CO 2 efflux are strongly affected by climate changes (Grundmann et al, 1995;Davidson et al, 1998).…”
Section: Resultsmentioning
confidence: 54%
“…Similar to the observation with the CO 2 efflux, our results showed that nitrification capacity was increased (Table 1). As soil nitrification is well known to be microbemediated (Grundmann et al, 1995;Lodhi et al, 2009), we examined the correlation between N gene abundance and nitrification in all of the soil samples. A strong positive correlation (r ¼ 0.70, Po0.001) was observed (Figure 4), suggesting that the increase of N cycle gene abundance in soils may partially explain the increase of the nitrification capacity in this study.…”
Section: Microbial Mediation Of Responses To Warmingmentioning
confidence: 99%
“…Production of N 2 O via heterotrophic nitrification is poorly understood because autotrophic and heterotrophic nitrification can occur simultaneously in a given soil and it is difficult to separate the end products of these two processes without using 15 N tracers (Matheson et al, 2003). Sufficient soil O 2 levels [(optimum at water filled pore space (WFPS) of 60%)], adequate NH 4 + concentrations, a favorable soil temperature above 5 o C (optimum 25 to 35 o C), and soil pH above 5 (optimum 7 to 9) are among the known soil and environmental conditions which control the rate of autotrophic nitrification (Linn & Doran 1984;Grundmann et al, 1995;Whitehead, 1995;Zaman et al, 1999a;Šimek., 2000;Zaman & Chang, 2004;Zaman et al, 2007;Saggar et al, 2009;Zaman et al, 2009;Zaman & Nguyen, 2010). Among these factors, NH 4 + and O 2 concentrations are considered the most critical factors affecting autotrophic nitrification (Zaman et al, 2007).…”
Section: Nitrificationmentioning
confidence: 99%
“…III) due to suppression of water uptake by roots. This higher soil moisture may have led to overestimating production and uptake rates [29]. However, Sierra [73] did not find a high response of mineralisation to an increase in soil moisture inside incubated cylinders of soil, and nor did Jussy [40] find such a response in laboratory incubations of this specific soil.…”
Section: Limits Of the In Situ Incubation Methodsmentioning
confidence: 97%